PERAN WANITA TANI DALAM KEGIATAN USAHATANI PADI SAWAH DI DESA SINDANGKASIH KECAMATAN RANOMEETO BARAT KABUPATEN KONAWE SELATAN - Arnisa Azahra; Hartina Batoa; Yoenita Jayadisastra (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The objective of this study is to ascertain the role of farm women in paddy rice cultivation activities in Sindangkasih Village, Ranomeeto Barat Subdistrict, South Konawe Regency.The population of this study comprises all farm women who play a role in assisting farmers in paddy rice farming activities, with a total of 25 individuals. The census method was employed to select the sample, resulting in a total of 25 informants. The collection of research data was conducted through observation, interview, and documentation methods, employing instruments in the form of questionnaires or interviews. The research variable encompasses the role of farm women in paddy rice farming activities, including land processing, seed selection, planting, care/maintenance, harvesting, and marketing. The analysis of research data was performed through quantitative descriptive analysis using the interval class formula. The results indicated that the role of farm women in paddy rice farming activities in Sindangkasih Village, Ranomeeto Barat Subdistrict, South Konawe Regency was classified as high, medium, or low, depending on the stage of the activity. Specifically, farm women's roles were classified as high for the stages of planting, maintenance, and harvesting; medium for seed selection and post-harvest; and low for land processing.